Multi-Method Approach in the Assessment of Alexithymia in Patients With Scleroderma: Use of Two Different Tools - Dattolo, Anna; Samela, Tonia; Abeni, Damiano; Pallotta, Sabatino; Sampogna, Francesca (Frontiers in Psychology, 2021)
Objective. Alexithymia is frequent in patients with some chronic dermatological conditions. The aim of the study was to measure the prevalence of alexithymia in patients with systemic sclerosis (SSc) using two different tools. Methods. Consecutive patients diagnosed with SSc were recruited at day hospital and hospitalization regimen. Alexithymia was measured using the self-administered questionnaire 20-item Toronto Alexithymia scale (TAS-20) and the semi-structured interview 24-item Toronto Structured Interview for Alexithymia (TSIA). Results. The study population consisted of 67 female patients, aged from 29 to 82 years. According to TAS-20, 22.4% of patients were alexithymic and 17.9% were borderline alexithymic. Also, in our sample mean TAS-20 value was 48.9 and TSIA mean value was 20.3Spearman’s correlation coefficient between TAS-20 total score and TSIA total score was 0.603. A high correlation was observed between TAS total score and the “Affective Awareness” (AA) scale of the TSIA. TSIA total score significantly correlated with the “Difficulty describing feeling to others” (DDF) scale of the TAS-20. The highest correlation between scales of the two instruments was that between TAS-20 DDF and TSIA AA (r=0.675). Conclusion. The prevalence of alexithymia in SSc patients was higher than in the general population, and similar to that of psoriasis patients. The measurements obtained using the TAS-20 and the TSIA were highly correlated. However, they also showed some diversities in the scales, indicating that they may measure different domains.